1966
DOI: 10.1111/j.1467-8306.1966.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Climates of the Conterminous United States: A Bioclimatic Classification Based on Man

Abstract: This study deals with human comfort expressed in a physio-climatic classification. Four physiological and psychological reactions of man to temperature, relative humidity, wind chill, and solar radiation are combined into two nomograms from which average human reactions can be deduced. Comfort and Wind Effect Indices are applied to meteorological data of the conterminous United States for July and January, daytime and nighttime, respectively. Maps combining both indices for July apply the classification on a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 23 publications
0
58
0
2
Order By: Relevance
“…It was shown that the combination of WCET and exposure duration was very well related to performance with correlations exceeding 0.9 for finger dexterity (formula [4]). Teichner 7) was one of the few who related dexterity to wind-chill.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the combination of WCET and exposure duration was very well related to performance with correlations exceeding 0.9 for finger dexterity (formula [4]). Teichner 7) was one of the few who related dexterity to wind-chill.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sunshine is, together with precipitation and wind, one of the elements that are most clearly perceived by the tourist. Therefore, the delimitation of thresholds for this parameter can be based on the preferences shown by tourists in surveys (Terjung 1966, Campbell & Beets 1977, Cunningham 1979.…”
Section: Daily Sunshinementioning
confidence: 99%
“…In this work we have used some of the most widely used comfort indices: Discomfort index (ID) [3], Wet Bright Bulb Index (WBGT) [4], and some charts such as Olgyay's Chart [5] and Terjung's Chart [6], as well as some recent indices such as Vinje's Cooling Power (PE) [7].…”
Section: Urban Planning Comfort and Environmentmentioning
confidence: 99%